Cloud computing system for small and medium corporations - Vijaya Arjunan, R.; Vinayaka Kamath, K. (International Journal of Engineering and Technology, 2017)
Cloud computing provides services that allocate infrastructure resources using the Internet as a medium and data storage on an external server. Small and medium corporations are the foundation of any flourishing economy for a growing nation which seeks new and innovative methods to reduce the way they manage their resources. Over a couple of decades, Information technology (IT) has created a significant impact in improving the lives of people and alsoon the global economy due to tremendous digital transformation. With the growth of the Small and medium corporations, IT is creating some real impact in enabling these industries to undergo adigital transformation of their business processes while they continue to grow. Small and medium enterprises (SME’s) are usually identified as the dominant force for the growth of any country's economy. In the cloud computing environment, the SME's need not have the in-house infrastructure so they can give up on any initial expenditure for setting up and instead they can utilize the resources available on the cloud and pay as per their requirement and usage.This paper presents the results of a comprehensive interpretation to research some of the most commonly used SaaS (Software-as-a-Service) implementations in the domain of Cloud Computing firstly to identify the weaknesses of the traditional computing approach for SME’s, and secondly to identify the aspects of these weaknesses that can be overcome by implementing cloud computing.In this paper, we provided the overview of various cloud computing models and literature survey of these models. This study extends to create an own cloud computing system for small and medium corporations. We will be using Software-as-a-Service (SaaS) approach and see how small and medium corporations can leverage on this for their business operations.